PENGARUH PENGETAHUAN, KETERSEDIAAN, PENGAWASAN DAN SANKSI TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA MEBEL DI PT. BORNEO MELINTANG BUANA EKSPORT, KABUPATEN SLEMAN (Berita Kedokteran Masyarakat (BKM), 2017)
ABSTRACKBackground: Workers have an obligation to use personal protective equipment at working area. The personal protective equipment has been determined based on risk but many workers of PT. Borneo Melintang Buana Eksport do not use the required protective equipment. This study aims to determine the effect of knowledge, availability, supervision and sanctions toward the use of personal protective equipment.Method: This research using quantitative method with cross sectional study design and 68 people as the subject. The instruments of this study are questionnaires and observation sheets. The independent variables were knowledge, availability, supervision and sanction while the dependent variable was the use of personal protective equipment. The statistical test used were chi-square and fisher exact with alpha 5%.Results: The results showed that there was a statistically significant effect between controlling the use of personal protective equipment (p value < 0.05) and no statistically significant effect between knowledge, availability and sanction on the use of personal protective equipment (p value > 0.05).Conclusions: There is a statistically significant effect between supervision toward personal protective equipment usage. Supervision needs to be maintained and improved by involving the workers as the supervisors.Keywords: Knowledge, Availability, Supervision, Sanction, Use of Personal Protective Equipment